Exploring Islamic Values in Midwifery Care: Exploring the Integration of Islamic Values in Midwifery care - Suryaningsih, Endang Koni; Lesdianti, Kiki; Marlinton, Septi; Nurhidayati, Siti (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Pregnant women who maintain psychological resilience during pregnancy and childbirth are less likely to undergo Cesarean sections due to anxiety. Incorporating Islamic principles—such as offering greetings and reciting "Bismillah" before procedures—can foster trust and rapport between patients and healthcare providers. Objective: This study explores how fifth-semester obstetrics students integrate Islamic values into maternal care at Universitas 'Aisyiyah Yogyakarta and Universitas Sebelas Maret, Surakarta. Method: A qualitative study was conducted from March to June 2024 at both universities. Data were gathered through in-depth interviews with nine obstetrics students and analyzed thematically to identify key themes. Results: Three main themes emerged: (1) Islamic values in obstetric care at Universitas 'Aisyiyah Yogyakarta; (2) Islamic values at Universitas Sebelas Maret; and (3) how students incorporate these values into their practice at both institutions. Students recited "Bismillah" and expressed gratitude to Allah before and after procedures, taught patients to pray, and encouraged acts of worship such as prayer and Quranic recitation (tadarus). These practices reflect a holistic approach that combines pregnancy education with spiritual support, promoting trust and spiritual well-being. Conclusion: Fifth-semester students at both universities demonstrated a strong commitment to faith-based obstetric care. Their integration of Islamic principles into clinical practice enhances the patient experience by fostering trust, spiritual comfort, and holistic support during pregnancy and childbirth.